The Relationship between Motivation and Incentives on the Performance of Integrated Service Post Cadres in Transmigration and Non-Transmigration Areas in the Lambale Community Health Center Work Area, North Buton Regency - Hasadyn, Hasadyn; Sunarsih, Sunarsih; Asri, Andi (Waluya The International Science of Health Journal, 2024)
Introduction: Initial observations carried out in the Lambale Community Health Center working area, North Buton Regency showed that from interviews with 10 posyandu cadres in transmigration and non-transmigration areas, the average result was that cadres who were inactive were caused by several things, including being busy with other jobs such as housewives and There are still cadres who do not understand their duties in integrated service posts. Method: This type of research is quantitative research with a cross sectional approach. Using a comparative study of transmigration and non-transmigration areas in the Lambale Health Center area, North Buton Regency, looking at the motivation and incentives principles of posyandu cadres. The population was 85 cadres and a sample of 39 used the Lemeshow formula with simple random sampling technique. Result: Based on the results of statistical tests using the Chi Square test, the results obtained were 0.005<α 0.05, H0 was rejected and Ha was accepted, indicating that there is a relationship between cadre motivation and the performance of Posyandu cadres in the Lambale Community Health Center working area, North Buton Regency. Based on the results of statistical tests using the Chi Square test, the results obtained were 0.000<α 0.05, H0 was rejected and Ha was accepted, indicating that there is a relationship between cadre incentives and the performance of Posyandu. Conclusion: There is a relationship between cadre motivation and incentives on the performance of posyandu cadres in the Lambale Health Center work area, North Buton Regency.